Farmakologiczne metody zwiększania efektywności zabiegów przetokowych - Szaflik, Jerzy; Zaleska-Żmijewska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Different antiproliferative agents: 5- fluorouracil, mitomycin C, growth factors antibodies, cyclosporine A, used as an adjunct to improve the success rate in filtering surgery and most common complications associated with them, are described.